Rancher viewpoint diversity in human–wildlife coexistence management: The case of jaguar–livestock interaction in the region of Calakmul, Mexico - Elías J. Gordillo‐Chávez; Claudia Villanueva‐García; Enrique Melo‐Guerrero; Mircea G. Hidalgo‐Mihart; Miguel Lizana‐Avia; Fernando Rodríguez‐López; Victor J. Colino‐Rabanal (People and Nature)
Abstract Protected areas in Latin America are typically surrounded by ranching landscapes, where large carnivores such as the jaguar (Panthera onca), co‐habit with ranchers, which potentially causes negative interactions. It is crucial, however, recognize that effective coexistence hinges on developing conservation policies that not only address these negative interactions but also embrace the diversity of the landowners' perspectives, aligning with the preferences of communities to prevent conservation conflicts. In this study, we conducted discrete choice experiments (DCE) with 196 ranchers in five localities in the Calakmul region to assess their preferences about four key attributes related to jaguar conservation: percentage of forests, livestock management practices, the number of desired jaguars and the willingness to invest in measures that promote coexistence between livestock and jaguars. Our research reveals that ranchers' preferences are diverse. Some favour increased forest cover and silvopastoral ranching, while others prefer reduced forest areas and the absence of jaguars. To address these diverse viewpoints and promote positive preferences, we must develop a comprehensive strategy considering the full spectrum of needs and preferences. Therefore, conservation incentives must be designed to address local communities' fundamental needs, such as education, healthcare, women's empowerment and cultural preservation. Participatory diagnostics involving local communities are imperative to accurately identify these needs. The observed heterogeneity of preferences in our study emphasizes the importance of integrating these diverse perspectives into conservation policies for a more balanced and equitable distribution of resources. Our findings demonstrate the value of DCEs in providing valuable information for developing more effective and socially acceptable jaguar conservation policies that consider diverse perspectives and the people's characteristics in our sample population. Read the free Plain Language Summary for this article on the Journal blog.